English Language Attitude of the Local Tourism Workers at Munggu Tourism Village Badung Regency Bali - Murdana, I Ketut; Paramita, Ratri (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2022)
The research aimed at studying and analyzing English language attitude of the local tourism workers at Munggu Tourism Village of Badung Regency Bali. The primary research data are directly collected from the research informan using the non-participatin observation, structured interview processes, and also from the research questionnaire completion. The informan were selected using non-probability sampling technique which are: purposive, snowball, and abundant sampling techniques with the total members of 30 samples are analysed. The research finding showed that 0,88% of the informan showed positive attitude toward English, from the genders point of view, the total numbers of 0,76% and 0,25% showed positive attitude toward English. Based on the tourism jobs the total members of informan showed positive attitude toward English